Patch Choice, Landscape Ecology, and Foraging Efficiency: The Zooarchaeology of Late Holocene Foragers in Western Argentina. Issue Volume 35:Issues 3(2015) (October 2015) - Wolverton, Steve; Otaola, Clara; Neme, Gustavo; Giardina, Miguel; Gil, Adolfo
Different but complementary foraging adaptations existed in the Payunia volcanic and the Andean highland (or mountain) subregions of southern Mendoza, Argentina during the late Holocene. We employ an evolutionary ecological perspective to study the zooarchaeology of foraging adaptations after 4000 BP. Seasonal exploitation of guanaco ( Lama guanicoe Müller) in the mountains appears to have been sustainable, which relates to high productivity of mountain river valley bottoms during the late Holocene. The mountains were a productive, seasonally available resource patch. A greater diversity of fauna in the Payunia subregion resulted in a different foraging strategy with larger diet breadth. Despite mounting evidence that human population growth occurred during the late Holocene, there is little evidence of resource depression of high-ranked resources, such as the guanaco. Application of foraging theory models in this context clarifies that hunting decisions occurred in the context of two factors, strategies informed by traditional ecological knowledge and the context of landscape ecology.